Handbücher zur Sprach- und Kommunikationswissenschaft / Handbooks of Linguistics and Communication Science Semantics Volume 3 - Maienborn, Claudia; von Heusinger, Klaus; Portner, Paul (De Gruyter, 2012)
Semantics; Linguistic; Theories; Generative and Cognitive Linguistics